Stochastic seismic response analysis of buried onshore and offshore pipelines - Bi, Kaiming; Hao, H.; Li, C.; Li, H. (Pergamon, 2017)
Previous studies on the seismic responses of offshore pipelines are not only very limited but also usually use earthquake ground motions recorded at the onshore sites as the inputs in the analyses due to the lack of seafloor earthquake recordings and the difficulty to predict seafloor seismic motions. This application may lead to erroneous predictions of offshore pipeline seismic responses, since it has been revealed that the existence of the seawater can significantly suppress the seafloor vertical motions near the P-wave resonant frequencies of the seawater layer. Moreover, the seawater layer can indirectly influence the seafloor motions by changing the water saturation and pore pressure of subsea soil layers, which in turn may obviously affect the propagation of seismic P-wave at the offshore site and therefore the pipeline seismic responses. This paper investigates the stochastic seismic responses of buried onshore and offshore pipelines. The direct and indirect influences of seawater layer on the seafloor seismic motions are explicitly considered by using the recently derived theoretical local site transfer functions. The mean peak seismic responses of buried onshore and offshore pipelines in the axial and lateral directions are stochastically formulated in the frequency domain. The differences between the onshore and offshore pipeline seismic responses are emphasized and the influences of seawater depth and water saturation level of the subsea site on the offshore pipeline responses are discussed.